Gender differences in the prevalence, correlated factors and comorbidity of depression in adolescents: a cross-sectional study in Shanghai, China - Yi Wang; Xiyan Zhang; Yan Li; Hongyun Qin; Xin Li (Frontiers in Public Health)
BackgroundPrior studies have reported gender differences in the prevalence, comorbidity rates and related factors of depression during adolescence. But the gender differences in depression vary across studies. Besides, the evidence from Chinese adolescent samples is limited. This study aimed to explore gender differences in the depression-related factors, the potential interactions of the associated factors and clinical features of comorbid depression and anxiety among Chinese adolescents.MethodsA cross-sectional study involving 3,510 participants aged 11 to 16 years from schools (private and public) in Shanghai was conducted with an anonymous paper-and-pencil questionnaire. Children’s Depression Inventory (CDI), Child Anxiety Related Emotional Disorders (SCARED), Strengths and Difficulties Questionnaire (SDQ) were used to evaluate depression, anxiety and behavioral and emotional difficulties, respectively. Logistic regression model was used to explore the possible correlated factors of adolescent depression and analyze the interactions of the risk factors.ResultsOur results showed that there was no gender difference in the prevalence rates of depression (χ2 = 0.047, p = 0.83), but the prevalence of depression in females began to exceed that of males at the ages of 15 and 16. The factors associated with depression varied by gender. Private school was a risk factor for depression only in boys (adjusted OR = 1.842 [95% CI, 1.286–2.636]), whereas girls from nuclear families (adjusted OR = 1.631 [95% CI, 1.156–2.300]) and other family structures (adjusted OR = 2.682 [95% CI, 1.502–4.788]) were more likely to experience depression compared to their peers in extended family structures. Interaction analyses showed there was a negative interaction between abnormal peer problems and 7th grade among boys (adjusted OR = 0.288 [95% CI, 0.086–0.951]). Furthermore, comorbidity rates of depression and anxiety were higher in girls than that in boys (χ2 = 14.457, p < 0.001). And girls with comorbidity showed increased SDQ peer problems scores (Z = −3.151, p = 0.002).ConclusionThe findings indicate it is important to develop gender-specific interventions for adolescent depression. And for boys, evaluating peer relationships may be particularly crucial in lower grades. Moreover, recognizing the gender-specific clinical features of comorbid depression and anxiety is important for appropriate clinical diagnosis and targeted treatment.